(untitled) (Clinics, 2011)
PURPOSE: The aim of this study was to evaluate the effect of dexmedetomidine on shivering during spinal anesthesia. METHODS: Sixty patients (American Society of Anesthesiologists physical status I or II, aged 18-50 years), scheduled for elective minor surgical operations under spinal anesthesia with hyperbaric bupivacaine, were enrolled. They were administered saline (group C, n = 30) or dexmedetomidine (group D, n = 30). Motor block was assessed using a Modified Bromage Scale. The presence of shivering was assessed by a blinded observer after the completion of subarachnoid drug injection. RESULTS: Hypothermia was observed in 21 patients (70%) in group D and in 20 patients (66.7%) in group C (p = 0.781). Three patients (10%) in group D and 17 patients (56.7%) in group C experienced shivering (p = 0.001). The intensity of shivering was lower in group D than in group C (p = 0.001). Time from baseline to onset of shivering was 10 (5-15) min in group D and 15 (5-45) min in group C (p = 0.207). CONCLUSION: Dexmedetomidine infusion in the perioperative period significantly reduced shivering associated with spinal anesthesia during minor surgical procedures without any major adverse effect during the perioperative period. Therefore, we conclude that dexmedetomidine infusion is an effective drug for preventing shivering and providing sedation in patients during spinal anesthesia.